Investigating the Human Capital within the Scope of Global Container Lines: A Content Analysis - Yıldız, Ramazan Özkan; Ayaz, İlke Sezin; Baran, Esra (Ordu Üniversitesi, 2018)
The purpose of this study is to examine the human capital indicators within the scope of container shipping industry. In order to reach the objective of the study a content analysis is carried out. The sample of study is determined as the top 5 ranked global container lines in Alphaliner Top100 list according to their market share. In the analysis judgmental sampling method is used. The human capital (HC) indicators obtained as a result of the literature review are used as the key words and search frame on the content analysis of web sites. According to findings of the study, some of the most frequently mentioned human capital indicators are “health and safety”, “training”, “experience”, “commitment”, “skill”, “recruitment”, “education” and “leadership”. It is determined that the main elements to which container lines give importance in their human capital approaches are as follows; the welfare, development and commitment of the employees. The findings of this study constitute a useful source for the human capital literature within the context of the global container shipping industry.

Bu çalışmanın amacı uluslararası konteyner endüstrisi kapsamında insan sermayesi göstergelerini incelemektir. Çalışmanın amacına ulaşmak için bir içerik analizi uygulanmıştır. Çalışmanın örneklemi, yargısal örnekleme yöntemiyle pazar paylarına göre Alphaliner Top100 listesinde yer alan ilk 5 global konteynır hattı olarak tespit edilmiştir. Literatür taraması sonucunda elde edilen insan sermayesi göstergeleri web sitelerinin içerik analizinde anahtar kelimeler ve arama çerçevesi olarak kullanılmıştır. Araştırmanın bulgularına göre, en sık rastlanan insan sermayesi göstergelerinden bazıları; "sağlık ve güvenlik", "yetiştirme", "deneyim", "bağlılık", "yetenek", "işe alma", "eğitim" ve "liderlik" olarak belirlenmiştir. Konteyner hatlarının insan sermayesi yaklaşımlarında önem verilen ana unsurların şunlar olduğu tespit edilmiştir; Çalışanların refahı, gelişimi ve bağlılığı. Bu çalışmanın bulguları küresel konteyner endüstrisi bağlamında insan sermayesi literatürü için yararlı bir kaynak teşkil etmektedir.
Uluslararası Konteyner Hatları Kapsamında İnsan Sermayesinin İncelenmesi: Bir İçerik Analizi